Estrogen pendulum in schizophrenia and Alzheimer's disease: Review of therapeutic benefits and outstanding questions - Androvičová, Renáta; Pfaus, James G; Ovsepian, Saak V (Neuroscience letters, 2021)
Although produced largely in the periphery, gonadal steroids play a key role in regulating the development and functions of the central nervous system and have been implicated in several chronic neuropsychiatric disorders, with schizophrenia and Alzheimer's disease (AD) most prominent. Despite major differences in pathobiology and clinical manifestations, in both conditions, estrogen transpires primarily with protective effects, buffering the onset and progression of diseases at various levels. As a result, estrogen replacement therapy (ERT) emerges as one of the most widely discussed adjuvant interventions. In this review, we revisit evidence supporting the protective role of estrogen in schizophrenia and AD and consider putative cellular and molecular mechanisms. We explore the underlying functional processes relevant to the manifestation of these devastating conditions, with a focus on synaptic transmission and plasticity mechanisms. We discuss specific effects of estrogen deficit on neurotransmitter systems such as cholinergic, dopaminergic, serotoninergic, and glutamatergic. While the evidence from both, preclinical and clinical reports, in general, are supportive of the protective effects of estrogen from cognitive decline to synaptic pathology, numerous questions remain, calling for further research.
Keywords: Animals; Neuroprotection; Alzheimerova nemoc; Adjuvant therapy; estrogeny; Cognitive deficit; lidé; Plasticity; zvířata; Estrogen Replacement Therapy; Estrogens; estrogenní substituční terapie; Animal models; Alzheimer Disease; Menopause; Schizophrenia; schizofrenie; Humans